Inflation and the Boom-Bust Cycle in Corporate Leverage - Brown, Brendan (Atlantic economic journal, 2019)
Financial engineering is an art, not a science. The core of the subject is how to camouflage increases in leverage as the source of raised earnings on equity capital. This article explores how and why demand for financial engineers grows globally under the influence of inflationary U.S. monetary policy and how a boom in their profession contributes importantly to the potentially devastating effect of monetary inflation on economic prosperity. It proceeds to consider the extent to which foreign countries, large or small, would take steps to counter their vulnerability to the financial engineers, with particular reference to the case of the emerging markets and Japan who have experienced at times the maximum impact. Of course, the most effective defense is monetary, but for many reasons detailed here, this has rarely been implemented.